Perceptions of Communicative Behaviour of Schizophrenics by Relatives in Nakuru Level Five Hospital in Nakuru County, Kenya - Maina, Joseph; Kirigia, Eliud Kiruji; Onyango, James Ogola (International Journal of English Literature and Social Sciences (IJELS), 2019)
Limited knowledge and devastating perceptions about mental illness remain a concern in various countries of the world, especially in developing countries. This lack of knowledge has been found in studies as a key cause of weird beliefs people have about mental illnesses (particularly schizophrenia). Generally, schizophrenics are widely misunderstood and stigmatized in Kenya. They are made fun of, blamed and criticized for their sickness. There is a dearth of information in the Kenyan context. This study sought to find out the cultural attributes associated with deviant language among trilingual schizophrenics in Nakuru Level Five Hospital. The study adopted a phenomenological qualitative design underpinned by the Multilingual Production Model. The main instrument of data collection was questionnaire and group focus discussion.Data were drawn from six health personnel and six relatives of the schizophrenics obtained through purposive sampling. The data were analyzed descriptively. The transcribed data were evaluated for social attributes linked to schizophrenia. The study’s findings indicate that superstitions; family living condition; stressful life events and divine are some of the cultural and belief systems associated with the trigger of schizophrenia for those predisposed to the condition. This study will enlighten linguists, psychologists, relatives and kin of the patients and teachers in all institutions of learning.